A scoping review on the association between early childhood caries and life on land: The Sustainable Development Goal 15. - Morẹ Nikẹ Oluwátóyìn Foláyana; Robert J Schroth; Duangporn Duangthip; Ola B Al-Batayneh; Jorma I Virtanen; Ivy Guofang Sun; Arheiam Arheiam; Carlos A Feldens; Maha El Tantawi (PLoS ONE)
Background The Sustainable Development Goal 15 (SDG15) deals with protecting, restoring, and promoting the sustainable use of terrestrial ecosystems, sustainably managing forests, halting and reversing land degradation, combating desertification and halting biodiversity loss. The purpose of this scoping review was to map the current evidence on the association between SDG 15 and Early Childhood Caries (ECC). Methods This scoping review was reported in accordance with the preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR) guidelines. Formal literature searches were conducted in PubMed, Web of Science, and Scopus in March 2023 using key search terms. Studies with the criteria (in English, with full text available, addressing component of life on land, focusing on dental caries in humans, with results that can be extrapolated to control ECC in children less than 6 years of age) were included. Retrieved papers were summarised and a conceptual framework developed regarding the postulated link between SDG15 and ECC. Results Two publications met the inclusion criteria. Both publications were ecological studies relating environmental findings to aggregated health data at the area level. One study concluded that the eco-hydrogeological environment was associated with human health, including caries. The other reported that excessive calcium was associated with the presence of compounds increasing groundwater acidity that had an impact on human health, including caries. The two ecological studies were linked to SDG 15.1. It is also plausible that SDG 15.2 and SDG 15.3 may reduce the risk for food insecurity, unemployment, gender inequality, zoonotic infections, conflict and migration; while SDG 15.4 may improve access to medicinal plants such as anticariogenic chewing sticks and reduction in the consumption of cariogenic diets. Conclusions There are currently no studies to support an association between ECC and SDG15 although there are multiple plausible pathways for such an association that can be explored. There is also the possibility of synergistic actions between the elements of soil, water and air in ways that differentially affect the risk of ECC. Studies on the direct link between the SDG15 and ECC are needed. These studies will require the use of innovative research approaches.